Green Product, Saluran Distribusi, dan Brand Image terhadap Keputusan Pembelian - Habib Husien Baharudin Al Ghozali; Agus Budi Purwanto (Jurnal Bisnis dan Ekonomi, 2019)
This study aims to determine whether green product, distribution channel, and brand image influence the purchasing decision of Nestle Pure Life drinking water in Semarang City.The population in this study were buyers of Nestle Pure Life drinking water in the city of Semarang. Samples taken as many as 100 respondents using the Probability Sampling method that is Random sampling because the taking of sample members from the population is done randomly regardless of the strata that exist and in the population. While data collection uses a questionnaire. The results of the analysis show that green product has a positive influence on sales, distribution channels have a positive effect on purchasing decisions, and brand image has a positive effect on purchasing decisions.